Tractates Pesahim and Yoma - Guggenheimer, Heinrich W. (Studia Judaica, 2013)
This volume of the Jerusalem Talmud comprises the fourth and fifth tractates of the Second Order. Pesahim introduces the prescriptions regarding Passover; Yoma covers regulations related to Yom Kippur, especially the role of the Kohen Gadol and the order of services. The tractates are vocalized by the rules of Rabbinic Hebrew with an English translation. They are presented with full use of existing Genizah texts and with an extensive commentary explaining the Rabbinic background necessary for understanding the texts.